Heaven as the Deus: Confucian Religiosity and the Confucian-Christian Dialogue Since the Late Ming (Journal for the Study of Religion and History (JSRH), 2025)
The religiously characterized concepts of Heaven (天) and Shangdi (上帝) found in pre-Qin Confucian classics served as the foundation for Confucian-Christian dialogue during the late Ming period. The Confucian understanding of “Heaven” varied across different historical eras. In the pre-Qin period, expressions such as duiyue (对越), linge (临格), zhaoshi (昭事), and shitian (事天) all possessed distinctly religious features. However, by the time of the Song Confucians, religious interpretations of “Heaven” were notably weakened. It was not until the late Ming, with the introduction of Catholicism, that the literati began to revive or reinforce Confucian religiosity, emphasizing Heaven’s function in reward and punishment. Missionaries, for their part, equated the Confucian concept of Heaven with the Christian God. Under the shared theme of “reverence for Heaven,” both East and West, Confucianism and Christianity, engaged in dialogue and exchange through the approach of “one Heaven, different interpretations” (一天各表). The interpretative ambiguity, pluralism, and openness inherent in the Confucian classics made such Confucian-Christian dialogue possible. However, as the Rites Controversy unfolded, these interpretive possibilities collapsed. The “one Heaven, different interpretations” approach exemplifying the Confucian-Christian dialogue of the Ming and Qing periods offers valuable insights for contemporary discussions on the Sinicization of Christianity and inter-civilizational exchange.